Sports performance analysis and the analyst in elite wheelchair basketball - Francis, J. (University of Worcester, 2018)
Despite the rise in accessibility of Sports Performance Analysis (SPA), limited attention has been given to understanding how it is used within disability sports. This thesis interpreted the impact of a SPA provision for a men's wheelchair basketball team and the role of the analyst throughout the Rio de Janeiro Paralympic Games cycle (2013-2017) using a mixed methods approach. Through discussions with wheelchair basketball staff, a novel valid and reliable team-specific SPA template was developed for elite men's wheelchair basketball. The template was used to identify the key determinants of team success by analysing 31 games from the 2015 European Wheelchair Basketball Championships. The analysis highlighted the importance of the status of the game at the beginning of a possession, the type of defensive systems faced by the team in possession and the line-up configurations used by the offensive and defensive team. Further analysis of field-goal shot attempts (1,144 shots) from the top five teams from the 2015 European Wheelchair Basketball Championships indicated the importance of the shooting player's shot position, shot location, shot type and shooting with least defensive pressure. The key findings from these initial studies were disseminated to the British Wheelchair Basketball (BWB) coaches, players and support staff. The data were presented in an attempt to aid the training regimes, the decision-making process of coaches and players, and selection choices, as well as informing upcoming game strategies. A comparison of the team and shooting performances of the men's BWB team during the 2016 Paralympic Games to the performances at the 2015 European Wheelchair Basketball Championships was completed. This comparison indicated the performances only partially aligned with the advice, however, quantifiable improvements were observed regarding the efficiencies of a number of areas. Following the 2016 Paralympic Games exploratory work was undertaken, moving away from the traditional positivist paradigm within the field to an interpretivist perspective, to understand if the coaches, players and support staff had elected to use the data from the initial studies. The experiences of the coaches, players, support staff and the analyst were thematically analysed to present a story of the participants' perceptions. Informed by the narratives, the establishment of trust was found to be key in cultivating relationships with coaches, players and support staff to increase awareness and buy-in of SPA. The arising power and micropolitical interplay between the coach, players and analyst can be softened through the development of rapport, which can, in turn, lead to an increase in the engagement with SPA by all stakeholders. Overall the findings of this thesis suggested regardless of how accurate the SPA data are at identifying the key determinates of success, without the buy-in of the coaches and the foundation of trust between all individuals within the SPA process, the marginal gains which SPA could unlock cannot emerge. Subsequently, a new model of how SPA can inform the coaching process is presented. The thesis also highlighted the importance of acknowledging that performance analysts should not just be seen as individuals who work and produce numbers but people who work with people and thus play an important role in making a direct and important contribution to elite wheelchair basketball performance.